STRATEGI DAN PROGRAM EKSPOR PRODUK KERANJANG ANYAMAN BAMBU “KALATHI APO BAMPOU” KE PASAR ASEAN - Nadila Putri Maharani; Eny Setyowati (Universitas Muhammadiyah Surakarta, 2023)
The Campus Merdeka Certified Internship Program (MBKM) is an initiative by the Ministry of Education and Culture (KEMENDIKBUD) that provides opportunities for students to gain experience through internships and independent studies. Through this program, students can sharpen skills relevant to their field of study through real projects and obtain certificates as evidence of their achieved competencies. The National Export School Foundation collaboratesin the Independent Study with Certification program under the Campus Merdeka Certified Internship Program (MBKM), which focuses on the theme